2013
DOI: 10.1016/j.tjog.2013.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intraumbilical vein oxytocin injection on third stage of labor

Abstract: It was concluded that intraumbilical vein administration of 10 IU (1 mL) oxytocin immediately after fetus delivery was clinically effective in shortening the third stage of labor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 10 publications
2
10
0
Order By: Relevance
“…In present study, it was also shown that women in the study group had significantly shorter duration of the third stage when compared with women in the control group. This is in accordance with the study of Nankali et al, (2013). In their study, they aimed to determine whether intraumbilical vein oxytocin injection reduces the need for manual removal of placenta and shortens the third stage of labor, in comparison with placebo.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…In present study, it was also shown that women in the study group had significantly shorter duration of the third stage when compared with women in the control group. This is in accordance with the study of Nankali et al, (2013). In their study, they aimed to determine whether intraumbilical vein oxytocin injection reduces the need for manual removal of placenta and shortens the third stage of labor, in comparison with placebo.…”
Section: Discussionsupporting
confidence: 68%
“…In their study, they aimed to determine whether intraumbilical vein oxytocin injection reduces the need for manual removal of placenta and shortens the third stage of labor, in comparison with placebo. In the study of Nankali et al, (2013) randomized clinical trial, 178 women with singleton pregnancy and normal delivery were studied in 1 year. Immediately after fetus delivery, oxytocin infusion (20 IU/L) was started in both groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Placental expulsion depends its separation from uterine wall, capillary hemorrhage, contractility of the uterine muscle, maternal effort, and gravity effect on the placenta [12]. Placenta delivery is generally completed within 15 minutes following the fetus delivery in 90% of parturient [10,13]. Two distinct methods are usually used to manage the 3 rd stage of labor.…”
Section: Introductionmentioning
confidence: 99%
“…Placental expulsion depends on the separation of the placenta from the uterine wall, capillary hemorrhage, uterine muscle contractile ability after placental separation, maternal effort, and gravity of the placenta (4,5). Separation of the placenta from the uterine wall is usually completed within 15 minutes in 90% of women after a fetal delivery (2,6). Prolongation of the TSL increases the development of PPH, which is responsible for one quarter of maternal deaths globally, one third of all pregnancy-related deaths in Africa and Asia, and approximately 140.000 deaths annually (7,8).…”
Section: Introductionmentioning
confidence: 99%